The Adverse Effect of Air Pollution with Polycyclic Aromatic hydrocarbon (PAH) on 8-OXO-DG and gene expression (HOGG1) in Midland Refineries Company-Daura Refinery Workers - Raghad H Al-Ani; Estabraq AR. Al-Wasiti (Institute of Medico-legal Publications Pvt Ltd, 2021)
Introduction: Polycyclic aromatic hydrocarbons (PAHs) are a group of different kind of hazardous organic chemicals which are considered to be the top of pollutants that released by petroleum industries exploration activities to the environment. PAH Metabolites that affect initiation of cancer by reaction with DNA are practically modified chemically by enzymes. PAH Mutagenic metabolites include radical PAH cations, diol epoxides, and quinones. Reactive oxygen species (ROS) mostly produce by routine oxidation processes in mitochondria is responsible for many types of DNA damage. The aim of study identify the DNA alteration due to air pollution by modulation of gene expression and regulatory gene Human 8-oxoguanine DNA Glycosylase (HOOG1) and association with 7,8-dihydro-8-oxoguanine (8-oxo-dg). Methods: there were 168 participants included in this study divided in three groups (control, office workers and in field workers) .PAH, 8-OXO-DG and gene expression (HOGG1) detected for each participant by GC/MS, competitive ELISA and quantitative-competitive reverse transcription-PCR respectively. Results: PAH were not detected in the blood of control group, and there was significant difference in the concentration of PAH between office and field workers. The concentration of (8-oxo DG) and (hOGG1) was significantly higher in field worker than in office worker and control group, significant difference was found between office workers and control. Discussion: It is observed that increased levels of PAH and its metabolites when exposed to polluted air. PAHs metabolism is associated with production of ROS as well as oxidative damaged. Among this damage, the most common lesion is (8-OHdG) .Increase in (8-OHdG) levels associated with increase oxidative stress and (HOGG1) gene. Conclusion: (a) increased PAH and its metabolites levels in serum causing high 8-OHdG and (HOGG1) expression levels in refineries workers (b) there is a correlation between 8-OHdG and hOGG1 expression with PAH.